Role of Islamic Education Teachers in enabling Students to Respond Global Challenges - NM, Siti Rahayu (Journal Intellectual Sufism Research (JISR), 2021)
This paper entitled "The Role of Islamic Education Teachers in Helping Students Respond to Global Challenges", is described specifically in the learning process in schools, especially in a global era that is full of various kinds of challenges. This paper is based on literature studies, for example about globalization, the description of rural and urban communities, as written by Eko Budiharjo in Urban Reform, about education, about learning, and others. Globalization is one of the foundations, because we live in the era of globalization, so a study of this will provide an overview of the times, for ISLAMIC EDUCATION (Islamic Education) teachers. A little study of rural and urban communities is also the basis of the study, because now there has been a shift in the way of life of the community towards urban communities. And also provides an overview, the differences between villages and cities, differences in value order, cultural order, mindset order to behavior patterns, especially students. This knowledge is needed by teachers to use as a basis for acting or making decisions. The study of education or learning, is a sure thing for teachers. This paper is also based on the experience and observations of the author, when he was a teacher several years ago, for approximately 20 years. Between experience, observations, and literature in the form of theoretical studies are mixed into writing.